Development Aid: The Anatomy of a Crisis - Koldo Unceta Satrustegui (Íconos)
The current study presents an interpretive framework on the crisis of development aid. The study begins with the analysis of some of its symptoms, centers on considerations about transformations that have operated during the last decades and have particularly affected the identity of aid (such as those related to the globalization of economic and social processes) and have affected the validity of the North-South paradigm as an interpretive model of conflicts over development. Finally, several aspects are addressed in relation to development aid objectives, instruments, and actors, demonstrating their collective influence in the debate over a possible readaptation and updating of development aid.